PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERTAHANAN NASIONAL (BPN) KOTA PEMATANGSIANTAR - Ambarita, Gita Theresia; Lie, Darwin; Efendi, Efendi; Sisca, Sisca (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The purpose of this study are: 1. To determine the description of work discipline and communication and the employee’s performance at Kantor Badan Pertanahan Nasional (BPN) Kota Pematangsiantar. 2. To determine the influence of work discipline and communication on employee’s performance at Kantor Badan Pertanahan Nasional (BPN) Kota Pematangsiantar simultaneously and partially. This research is done with library research and field research. The data types are cualitative and quantitative data, the data sources are primer and secondary data. The population in this research is as much as 31 respondents. The data collection is done with questionnaire, interview and documentation. Technical analysis used is multiple linear regression, coefficient of correlation, coefficient of determination and hypothesis test F test and t test. The results of the study can be summarized as follows: 1. work discipline, communication and employee’s performance is good. 2. The results of regression analysis is Ŷ= 34,319 + 0,445X1 + 0,638X2 it means that work discipline and communication had a positive influence on employee’s performance. 3. The results of correlations analysis get value r= 0,826, it means that there is a high and positive correlation between work discipline, communication with employee’s performance. Further obtained coefficient of determination (R) = 0.682 means the level of employee’s performance can be explained as much as 68,2% by work discipline and communication. 4. The results of hypothesis test H0 is rejected, it means that work discipline and communication had a positive and significant influence on employee’s performance simultaneously and partially. The suggestion of this research is to improve the work discipline, 1. the leadership must be more firmly to give sanction for anyone who violates the rules. 2. To influence communication, the leadership and the subordinates must create good relations in order to achieve a conducive working environment. 3. to optimize the employee’s performance, the leadership have to apply the rules so that employees can implement the rules properly. Keywords: Work Discipline, Communication and Employee’s Performance